Erythrocyte osmotic fragility of pigs administered ascorbic acid and transported by road for shortterm duration during the harmattan season - A. Y. Adenkola; J. O. Ayo; A. K. B. Sackey; A. B. Adelaiye (African Journal of Pig Farming, 2016)
The experiment was carried out with the aim of investigating the effect of an antioxidant ascorbic acid on erythrocyte osmotic fragility of pigs transported by road for 4 h during the harmattan season. 16 pigs administered with ascorbic acid at the dose of 250 mg/kg per os and individually served as experimental animals and 13 others administered orally with sterile water were used as control animals. The animals were then transported for 4 h at a speed of 40 - 50 km/h covering a distance of 140 km. Blood samples for erythrocyte osmotic fragility determination which was done using standard procedure, were taken early in the morning a day before transportation, immediately after and a week after transportation. Erythrocyte osmotic fragility decreased significantly (P < 0.05) at NaCl concentration of 0.85, 0.80 and 0.70% in both experimental and control pigs following road transportation and the difference in the post-transportation values was higher (P < 0.05) in experimental compared to control pigs. The results indicated that ascorbic acid protected the integrity of the erythrocyte membrane in experimental pigs administered ascorbic acid following road transportation as demonstrated by lower percentage haemolysis immediately after road transportation and thus may alleviate the risk of increase in haemolysis due to road transportation stress in pigs during the harmattan season.